Problems encountered in a dissertation writing among undergraduate quantity surveying students in UiTM / Nur Ain Azizi and Siti Nor Faizah Ab Malek - Azizi, Nur Ain; Ab Malek, Siti Nor Faizah (2020)
throughout their academic writing journey. The objectives of this research are to identify the challenges in writing a dissertation and to determine the implications that arise caused by the challenges among undergraduate Quantity Surveying students. A total of 175 students from 5th and 6th-semester were participated in the study. The quantitative research design was being adopted to collect data by using a questionnaire that consists of both close-ended and Likert Scale questions. All of the data collected were analyzed using IBM SPSS Statistics 25. The method used is descriptive statistics of frequency, tables, and percentages. Then, rank cases also being implemented to transform the data into data ranking. The results of the study revealed that access to resources, the bad relationship between undergraduates and supervisor, plagiarism, poor time management, lack of understanding in Literature Review writing, low proficiency in English language, graduates having no interest in the research topic, and insufficient knowledge on referencing and citation become challenges for the most of undergraduates. However, limited access to resources showed the greatest percentage compared to other challenges. The study recommended that further study be carried out with undergraduate students from different universities regarding the other challenges, implications, and adoption of problem-solving.